O conceito de tecnologia em Álvaro Vieira Pinto e suas implicações para a educação profissional: uma abordagem dos Institutos Federais - Sandeski, Vicente Estevãm (2016)
The aim of this research is to study the professional education as practiced by the Federal Institutes of Education, Science and Technology created in 2008, due to the strong economic market demand for skilled workforce. This paper investigates the possibility to overcome the historical technicist education controlled and oriented by the market interests, by means of a critical and emancipatory education. The issue discussed in this paper is to have a critical and emancipatory professional education developed at the Federal Institutes, transcending the concepts of conventional technology. For such approach, the work of Álvaro Vieira Pinto was referred to, entitled O Conceito de Tecnologia (The Concept of Technology), which keeps a strict relation with the national reality. The search in this material, based on the professional education grounds of the federal institutes, concerned: education, research and extension, at the first stage, to understand the ideological structure of the public policies with its controls and limits for an emancipatory education; next, by comprehending Vieira Pinto´s reality in the concepts of development, technology and emancipation, to understand the path to rebuild critical and emancipatory education through the analysis of the concept of technology by Vieira Pinto. The research demonstrates the interiorization of the Federal Institutes and their increase of access to working classes, explaining the educational procedures to develop an overcoming and emancipatory education, which demands a professional education that overcomes the market interests and which is working-class oriented. The critical and emancipatory technical-scientific education concept establishes itself through an education that identifies the correlations of forces and that commits itself to the working class. In this study, both the theoretical data of Vieira Pinto and the acting of the Federal Institutes are articulated, identifying how they can contribute to educate professionals able to offer consistent answers in the regions where they are inserted. To that end, we analyzed the public policies of technological education, as well as their materialization in the legislations and guidelines that ground and regulate the professional education action, from 2013 to 2014. The period comprehended for this analysis is based on categories explained by Vieira Pinto, in the years of 1955 to 1964, a period of great national confluence of the ideas and the professional acting of such author. Finally, the methodological procedure adopted in this paper will consist of a bibliographical research of the work of Vieira Pinto, O conceito de tecnologia, as well as complementation for explaining education within the Brazilian context from 2003 to 2014, which is specific for technology and its outcomes in education. The data collected in the literature were compared with the education proposal of the Federal Institute of Education, Science and Technology of Paraná - IFPR, which led to obtain reasonings from the evidence emerged in the analysis.